Should screening of genital infections be part of antenatal care in areas of high HIV prevalence? A prospective cohort study from Kigali, Rwanda, 1992-1993. The Pregnancy and HIV (EGE) Group. Issue 4 (August 1995) - Leroy, V; De Clercq, A; Ladner, J; Bogaerts, J; Van de Perre, P; Dabis, F
Abstract : OBJECTIVE--To study the prevalence and incidence of genital infections and their association with HIV-1 infection among pregnant women in Kigali, Rwanda. SUBJECTS AND METHODS--HIV+ and HIV- pregnant women were followed prospectively during the last three months of pregnancy. At enrolment, syphilis test (RPR) on blood sample, Chlamydiae trachomatis ELISA test on cervical smear, laboratory gonococcal culture, trichomonas and candida direct examination, CD4 lymphocyte count were performed. At each monthly follow-up clinic visit until delivery, genital infections were screened in the presence of clinical signs and symptoms. RESULTS--The HIV seroprevalence rate was 34.4% (N = 1233), 384 HIV+ women and 381 HIV- women of same parity and age were enrolled. Prevalence of genital infections at enrolment was generally higher in HIV+ women than in HIV- women: syphilis, 6.3% versus 3.7% (p = 0.13); Neisseria gonorrhoea, 7.0% versus 2.4% (p = 0.005); Trichomonas vaginalis, 20.2% versus 10.9% (p = 0.0007); Chlamydia trachomatis, 3.4% versus 5.5% (p = 0.21); Candida vaginalis, 22.3% versus 20.1% (p = 0.49). Until delivery, the relative risk of acquiring genital infections was also higher in HIV+ women than in HIV- women: 1.0 for syphilis (95% CI: 0.5-2.2), 3.7 for Neisseria gonorrhoea (1.0-13.3), 2.6 for Trichomonas vaginalis (1.5-4.6) and 1.6 for Candida vaginalis (1.1-2.4). CONCLUSION--In the context of high HIV-1 seroprevalence among pregnant women, prenatal care should include at least once screening for genital infections by clinical examination with speculum and a syphilis testing in Africa.